(untitled) (Journal of Solar Energy Research Updates, 2024)
Abstract: Solar energy systems can be an alternative to fossil fuels and are vital for a sustainable environment. It is promising that solar chimney power plants (SCPPs), which are among the solar energy systems, provide 24-hour power output (PO) and can work integrated with other systems. This study is based on the Manzanares pilot plant (MPP) and demonstrates satisfactory performance with an additional heat source to be integrated into the ground of the system during hours when solar radiation is weak. The performance of the system at different source temperatures is compared with the reference case, with the model verified using the RNG k-ε turbulence model through a 3D CFD study. In fact, it is seen that the PO of the system, which yields a PO of around 10 kW at 200 W/m2 solar radiation in the reference case, exceeds 80 kW with a source temperature of 200°C. From the results, it can be noticed that the system can also output power in the evening hours when there is no sun. With an additional heat source of 200°C during non-sunlit hours, the system gives more than 75 kW PO. This PO is 50% more than the maximum PO of 50 kW in the reference case.